Geomorfologi Daerah Mananggu dan Sekitarnya, Kecamatan Mananggu, Kabupaten Boalemo, Provinsi Gorontalo - Kayambo, Muhammad Ridho; Arifin, Yayu; Akase, Noviar; Uno, Djamal Adi Nugroho (-, 2025)
This research was conducted in the Mananggu area and its surroundings, Mananggu District, Boalemo Regency, Gorontalo Province. The study aims to map the geological conditions and identify the characteristics of geomorphology and geological structures developed in the area. The methods employed included surface geological mapping for field data collection, followed by laboratory analyses. Geomorphologically, the research area is divided into two units: the Volcanic Hills Unit and the Structural Hills Unit. The stratigraphy consists of the Eocene-Oligocene Porphyritic Andesite Unit (Tinombo Formation) and the Pliocene Granite Unit (Bumbulan Granodiorite Formation) acting as an intrusive body. The geological structures are controlled by a transtensional regime resulting from compression, manifested as NW-SE shear joints, right normal slip faults, and normal right slip faults. The landscape evolution is strongly influenced by the interplay between the resistance of the igneous lithologies and the active tectonic deformation that shapes the drainage patterns and slope configurations.